(untitled) (Research, Society and Development, 2021)
This study presented the management plan in the honey commercialization chain in the interior of the state of Paraíba. The company that intends to open will have the fictitious name of MEL ORGANIC POMBALENSE. It will differentiate itself from competitors as it will offer consumers organic products. The main reason for this proposal is that currently there is no company specialized in the region of Pombal certified organic honey, or at least not in evidence or quantity, that develops a similar work, so I believe that these differentials can add value to the sales process, creating a loyal portfolio of satisfied customers, ensuring good profitability, success and business prospecting. The focus of the company will be a premium service of high quality for the market of organic honey, nowadays lacking a professional management and with focus on the satisfaction of the client. We will have direct sales of products in retail for customers. It was concluded that when selling honey on the market, we need to take into account a number of issues that we can not ignore is that very few traders who do not have economic plans and therefore end up failing, so we must have an economic plan also defined for this type of business selling honey.